Medullary GABAergic mechanisms contribute to electroacupuncture modulation of cardiovascular depressor responses during gastric distention in rats - Tjen-A-Looi, Stephanie C. (American Physiological Society, 2013)
Electroacupuncture (EA) at P5–P6 acupoints overlying the median nerves typically reduces sympathoexcitatory blood pressure (BP) reflex responses in eucapnic rats. Gastric distention in hypercapnic acidotic rats, by activating both vagal and sympathetic afferents, decreases heart rate (HR) and BP through actions in the rostral ventrolateral medulla (rVLM) and nucleus ambiguus (NAmb), leading to sympathetic withdrawal and parasympathetic activation, respectively. A GABA(A) mechanism in the rVLM mediates the decreased sympathetic outflow. The present study investigated the hypothesis that EA modulates gastric distention-induced hemodynamic depressor and bradycardia responses through nuclei that process parasympathetic and sympathetic outflow. Anesthetized hypercapnic acidotic rats manifested repeatable decreases in BP and HR with gastric distention every 10 min. Bilateral EA at P5–P6 for 30 min reversed the hypotensive response from −26 ± 3 to −6 ± 1 mmHg and the bradycardia from −35 ± 11 to −10 ± 3 beats/min for a period that lasted more than 70 min. Immunohistochemistry and in situ hybridization to detect c-Fos protein and GAD 67 mRNA expression showed that GABAergic caudal ventral lateral medulla (cVLM) neurons were activated by EA. Glutamatergic antagonism of cVLM neurons with kynurenic acid reversed the actions of EA. Gabazine used to block GABA(A) receptors microinjected into the rVLM or cVLM reversed EA's action on both the reflex depressor and bradycardia responses. EA modulation of the decreased HR was inhibited by microinjection of gabazine into the NAmb. Thus, EA through GABA(A) receptor mechanisms in the rVLM, cVLM, and NAmb modulates gastric distention-induced reflex sympathoinhibition and vagal excitation.